(untitled) (Revista de Ciências Agroveterinárias, 2025)
The definition of the minimum distance between the soybean sowing line and the orthotropic branch in intercropping with the coffee tree in formation guided the objectives of this research. The experiment was conducted in the demonstration area of the Federal University of Uberlândia, Monte Carmelo Campus, Minas Gerais. The coffee trees were planted in March 2021, with a spacing of 3.5 m between rows and 0.6 m between plants, using the IPR 100 cultivar. Soybeans were planted between coffee tree rows in November 2021, cultivar LG 60162IPRO, with a spacing of 0.4 m between rows and 14 seeds per linear meter. Only the coffee trees were irrigated using a drip system, with spacing between drippers of 0.6 m and a flow rate of 2.1 L h-1. The intercropping configured five management methods with soybean planting rows and distance from the last row to the orthotropic stem: T1: control without soybeans, T2: 2 rows - 1.55 m, T3: 4 rows - 1.15 m, T4: 6 rows - 0.75 m, and T5: 8 rows - 0.35 m from the coffee tree. Each plot consisted of five coffee plants. The following were evaluated in the coffee trees of the three central plants: length, width, and thickness of two leaves per plant, chlorophyll index (SPAD 502), leaf temperature, stomatal count, length of a pair of plagiotropic branches located in the middle third of the coffee tree, number and distance of internodes, and number of primary plagiotropic branches. Soybeans planted between coffee trees did not alter the development pattern of the leaves and branches of Coffea arabica L. when kept at distances greater than 0.75 m from the coffee tree stem. It is suggested that this is the minimum critical tolerance distance for coffee trees without them developing mechanisms to avoid shading and altering their growth pattern.